On the issue of three-dimensional political security of the political systems of post-Soviet societies - Aleksanyan, Ashot (YSU Journal of International Affairs, 2021)
The relevance of the research topic of this article lies in the fact that the transformations and market relations of the post-Soviet countries constantly give rise to various threats of an economic, social and political nature in relation to political parties, CSOs and individuals. At the same time, public policy as a system of reasonable measures to limit the negative consequences of transformation and market activity is designated as political security, because its actor is mainly public authority, which defines all its actions as political actions using political tools. However, comparative analysis in post-Soviet studies is more focused not on political security, but on national security, as a system for protecting the vital interests of the individual, society and the state, while in the theoretical aspect it is more correct to talk about political security as a set of various measures of public authorities aimed at producing relations that do not threaten the individual, society and the state. On the other hand, the relevance of the study also lies in the fact that national security is presented in political studies as a system of civiliarchic protection, which has a biopolitical character and comes from an effective system of checks and balances. Whereas security is also dynamic in nature, that is, it depends on the state of the actor, on his position in the political system of existing institutions, relations, consciousness, culture, values, norms, traditions, etc. At the same time, security in post-Soviet studies is considered one-sided, ideas about it are formed mainly from expert assessments that do not take into account the social, economic, political and cultural position of the actors. Comparative analysis of political security is carried out with less intensity than other spheres of biopolitics. The circle of post-Soviet researchers involved in political security in recent years is not as wide as required
Keywords: political security; political security space; political security time; political security speed; political system; post-Soviet societies; transformation; civiliarchy; civil society; public policy; culture